Odpowiedź :
(2∛2)³/6=2³*(∛2)³/6=[2*2*2*∛2*∛2*∛2]/6=
[8*∛(2*2*2)]/6=[8∛8]/6=8*2/6=16/6=2 i 2/3
[8*∛(2*2*2)]/6=[8∛8]/6=8*2/6=16/6=2 i 2/3
(2∛2)³
_______
6
pierwsiatek trzeciego stopnia i do potegi 3 sie anuluja. Musimy spotegowac obie liczby.
2³ x ∛2³ = 2³ x 2 = 8 x 2 = 16
___________________________
6
16 ÷ 6 = 2 ⅔
_______
6
pierwsiatek trzeciego stopnia i do potegi 3 sie anuluja. Musimy spotegowac obie liczby.
2³ x ∛2³ = 2³ x 2 = 8 x 2 = 16
___________________________
6
16 ÷ 6 = 2 ⅔
2 x 2 x 2 x 2 16 2
-------------- = -------------= 2 ---
6 6 3
(2 i dwie trzecie)
-------------- = -------------= 2 ---
6 6 3
(2 i dwie trzecie)